Poisoning the Student Mind?: The Student Christian Movement at the University of Toronto, 1920-1965 - Gidney, Catherine (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1997)
AbstractHistorians have documented the interlocking nature of student culture and religious life in nineteenth-century higher education; in contrast, after World War I religion has generally been ignored, or portrayed as disappearing from the academy and broader life. An investigation of the Student Christian Movement, however, suggests that by combining liberal theology with left-wing politics it became an influential religious force on campus well into the twentieth century. Reflecting a fairly homogeneous student population, supported by faculty and the administration, and articulating the temper of the times, the SCM served as the public voice of religion on campus. Only in the 1950s, as new social phenomena emerged, such as divisions among Protestants, the rise of agnosticism, and the creation of secular political organisations, did the SCM begin to lose its cultural authority on campus.